2020
DOI: 10.3390/ijms21144940
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Like Activity of HSPB5: The Effects of Quaternary Structure Dynamics and Crowding

Abstract: Small heat-shock proteins (sHSPs) are ATP-independent molecular chaperones that interact with partially unfolded proteins, preventing their aberrant aggregation, thereby exhibiting a chaperone-like activity. Dynamics of the quaternary structure plays an important role in the chaperone-like activity of sHSPs. However, relationship between the dynamic structure of sHSPs and their chaperone-like activity remains insufficiently characterized. Many factors (temperature, ions, a target protein, crowding etc.) affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 109 publications
0
16
0
1
Order By: Relevance
“…Earlier we showed a significant increase in the size of αB-Cr at 48 °C under crowding conditions arising from the presence of 1 M TMAO and/or other crowding agents [ 39 ]. The estimated number of subunits in the αB-Cr oligomer increased from 22-mers up to 50-mers under conditions of mixed crowding created by 1M TMAO + PEG [ 34 , 39 ]. Grosas and colleagues also reported an increase in the size of αB-Cr under crowding conditions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier we showed a significant increase in the size of αB-Cr at 48 °C under crowding conditions arising from the presence of 1 M TMAO and/or other crowding agents [ 39 ]. The estimated number of subunits in the αB-Cr oligomer increased from 22-mers up to 50-mers under conditions of mixed crowding created by 1M TMAO + PEG [ 34 , 39 ]. Grosas and colleagues also reported an increase in the size of αB-Cr under crowding conditions [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we studied the effect of Arg and Bet on αB-Cr and its PPIs with target protein and tried to determine the initial stoichiometry of the chaperone–client complex and the effect of Arg and Bet on this value at different stages of the enzyme aggregation. For the research, we chose a well-studied test system based on the thermal aggregation of glycogen phosphorylase b (Ph b ) at 48 °C [ 33 , 34 ]. Previously it was shown that Arg and Bet acted in opposite directions on Ph b aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that a flexible dynamic structure is required for the functioning of αB-crystallin. The equilibrium between oligomeric forms is very sensitive to changes in the cellular environment and crowding conditions [ 47 , 48 ]. In the eye lenses, there is a very delicate pattern of interactions among α-crystallin and its other natural partners, such as beta- and gamma-crystallin [ 49 ], so that as a result of the structural alteration, a slightest change in these interactions is expected to cause important optical focusing problem, leading to development of the visual perturbation [ 43 – 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it can be assumed that crowding conditions affect both the kinetics and thermodynamics of interactions between macromolecules, including protein folding and aggregation [ 119 , 120 , 121 ]. Since crowding has a strong effect on protein–protein interactions, its influence on the conformation and self-association of chaperones, interaction of chaperones with target proteins, and the aggregation of the target proteins should also be taken into account [ 122 ].…”
Section: Mechanisms Of the Formation Of Misfolded Proteinsmentioning
confidence: 99%